The approach of incremental adjustment, guided by heart rate variability metrics, in the coaching of elite swimmers - Pankov D.A. (Theory and Practice of Physical Culture, 2024)
Abstract Objective of the study was to assess the effectiveness of the Variсard system in optimizing the training regimen for elite swimmers. Methods and structure of the study. 30 qualified athletes took part in the observation: 10 masters of sports, 14 international masters of sports, 6 honored masters of sports. The task was to use HRV indicators in training management over a selected period, the same for the control and experimental groups. The study used the VARICARD complex and the ISCIM6 program. Results and conclusions. The findings of the research demonstrated the success of the «sitting position» scenario in accordance with the outlined monitoring procedure. The significance of the data collected enables the creation of a more precise training program.